“Mbya retxãi Opy tekoaxy mongy'a oa” : a manutenção da saúde Guarani-Mbya na Casa de Reza - Silveira, Teresa Cristina (Universidade Federal de São Carlos, 2011)
This ethnography proposes a reflection on the meaning of the concept of “helth maintenance” among the Guarani-Mbya people who live in the Indigenous Land Ribeirão Silveira, located at the coastal region of the state of São Paulo. From the presentation of the native notion of embodiment, wich is constituted through everyday practies of its manufacture and the rituals performed in Opy (cerimonial House) this work wants to show how the native people understands the Person notion.
Keywords: Guarani-Mbya; Manutenção da saúde; Xamanismo; Helth maintenance; Shamanism; CIENCIAS HUMANAS::ANTROPOLOGIA